Siting Sudaneseness: Territory, Practice, and Identity in Aragi - Curley, Bjorn (Refuge: Canada's Journal on Refugees, 2011)
The word “aragi” refers to a type of crude, distilled alcoholic drink brewed by Sudanese people throughout Sudan and bordering countries as well as in smaller Sudanese communities around the world. To the people of Sudan residing in neighbouring Egypt, however, aragi is more than a simple beverage; it is a cultural artifact whose value lies in its material and empirical embeddedness in social practice. This paper investigates the symbolic role that aragi plays in the production of identity among displaced Sudanese living in Cairo, Egypt. For Sudanese migrants in Egypt, aragi acts as a signifier, both linguistic and cultural, of their identity. This migrant identity is inhabited and generated through various practices involving aragi, within the social, spatial, and material spheres. In Egypt, Sudanese identity and aragi (as a cultural object) are ethnographically observed to be contextually and semiotically bound through their mutual signification in the word “aragi.” Herein, I will explore how the word “aragi” reflects and articulates social domains of inclusion and exclusion within an identity construed as distinctly Sudanese.